EVIDENCE ON AUDIT COMMITTEE COMPOSITION AND AUDIT COMMITTEE EFFECTIVENESS AMONG LISTED COMPANIES IN THE JAKARTA STOCK EXCHANGE - Utama, Siddharta; Leonardo Z., F (UI Scholars Hub, 2004)
The purpose of this study is to provide empirical on audit committee composition and audit committee effectiveness (ACE), based on a survey of audit committees of publicly listed companies in the Jakarta Stock Exchange. The study finds that the majority of the companies comply with the JSX requirement about the minimum number of audit committee member (3 persons), their independence, and their competence (finance or accounting background). However, this study finds that audit committees are not yet effective in their authority, resources, and efforts. The interaction of audit committee with external auditors is the least effective while the communication to the board of commissioners and shareholders is the most effective. The interaction of audit committee with internal auditors and monitoring on compliance are also ineffective.